2012
DOI: 10.1021/jm300670q
|View full text |Cite
|
Sign up to set email alerts
|

Designing Allosteric Regulators of Thrombin. Monosulfated Benzofuran Dimers Selectively Interact With Arg173 of Exosite 2 to Induce Inhibition

Abstract: Earlier, we reported on the design of sulfated benzofuran dimers (SBDs) as allosteric inhibitors of thrombin (Sidhu et al. (2011) J Med Chem 54: 5522-5531). To identify the site of binding of SBDs, we studied thrombin inhibition in the presence of exosite 1 and 2 ligands. Whereas hirudin peptide and heparin octasaccharide did not affect the IC50 of thrombin inhibition by a high affinity SBD, the presence of full-length heparin reduced inhibition potency by 4-fold. The presence of γ’ fibrinogen peptide, which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 50 publications
3
68
1
Order By: Relevance
“…In these assays, the concentration of an anticoagulant required to double the clotting time of human plasma is measured using a fibrometer, as described in our earlier work. 12 The best hit, 1 , was selected for these studies. A 2-fold increase in PT and APTT required 606 and 550 μM concentrations of 1 , respectively suggesting useful anticoagulant potency of this initial hit (Fig.. 7).…”
Section: Prolongation Of Plasma Clotting Timementioning
confidence: 99%
See 3 more Smart Citations
“…In these assays, the concentration of an anticoagulant required to double the clotting time of human plasma is measured using a fibrometer, as described in our earlier work. 12 The best hit, 1 , was selected for these studies. A 2-fold increase in PT and APTT required 606 and 550 μM concentrations of 1 , respectively suggesting useful anticoagulant potency of this initial hit (Fig.. 7).…”
Section: Prolongation Of Plasma Clotting Timementioning
confidence: 99%
“…Enzyme kinetic studies showed an allosteric inhibition phenomenon, while later studies with site-directed thrombin mutants identified the site of binding to a hydrophobic region close to Arg173, a site encompassed within exosite II. 12 This site of binding is a new discovery and is likely to be a promising avenue for anticoagulant drug discovery.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…27 This gave rise to the possibility of designing molecules that specifically target the hydrophobic (hP) domain surrounding the heparin-binding site (HBS) of proteins. In fact, coagulation enzymes possess hP domains of varying sizes around their strongly electropositive HBSs.…”
Section: Introductionmentioning
confidence: 99%